2021
DOI: 10.1088/1755-1315/771/1/012017
|View full text |Cite
|
Sign up to set email alerts
|

The effect of plastic debris attachment to the health of branching corals in Kelapa Dua Island, Thousand Islands

Abstract: Plastic marine debris are a potential threat to the life of marine organisms such as corals. This study aimed to analyze the effect of different plastic waste attachments on the bleaching rate and the health of branching corals at Kelapa Dua Island. Branching coral colonies consisted of 15 fragments of Porites cylidrica at the water depth of 80-90 cm, then treated with plastic waste (control, clear plastic, sack plastic, packaging plastic, and black plastic) for four days. Determination of color changes in cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Lamb et al (2018) found more than 11 billion plastic items entangled with coral reefs in the Asia-Pacific, and suggested that coral disease outbreaks increase when corals are entangled with plastic. Decreased light intensity from being covered by plastic debris has been documented to effect branching coral health and lead to coral bleaching (Muhammad et al, 2021). Field research in Kho Tao, Thailand, found that coral underneath a fishing net suffered the most damage (Valderrama Ballesteros et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Lamb et al (2018) found more than 11 billion plastic items entangled with coral reefs in the Asia-Pacific, and suggested that coral disease outbreaks increase when corals are entangled with plastic. Decreased light intensity from being covered by plastic debris has been documented to effect branching coral health and lead to coral bleaching (Muhammad et al, 2021). Field research in Kho Tao, Thailand, found that coral underneath a fishing net suffered the most damage (Valderrama Ballesteros et al, 2018).…”
Section: Introductionmentioning
confidence: 99%